Acute intermittent porphyria with complications arising from late diagnosis in a pediatric patient - Cunha, Gabriel Veloso; Gonçalves, Suziane Soares; Silva, Luana Cicília Sousa da; Fontes, Tânia Maria de Souza; Silva, Luciano Máximo da (Medicina (Ribeirao Preto), 2018)
Porphyria is a rare disease, consequence of enzymatic deficiencies associated with heme group biosynthesis. The aim of this report is to describe a case of acute intermittent porphyria crisis in a 15-year-old patient who progressed rapidly with tetraplegia and chronic terminal renal failure, as well as severe neuropsychiatric disorders. It represents an entity of difficult diagnosis due to the lack of specificity of the clinical findings. At admission, creatinine was 6.44 mg / dL and urea was 103 mg / dL. Significant neurological deficit and chronic renal failure are rare complications, arising from late diagnosis and treatment. A greater degree of clinical suspicion is fundamental that treatment be started immediately after diagnosis, due not only to short-term morbidity but also to possible deleterious permanent effects.